Data SPARC - THIBODEAU, Benoit; Tim Staples; Ruth Thurstan; Keegan Carvalho; John Doherty; John Pandolfi; James Scourse; Lin Liu; Ngai Hang Chan
The North Atlantic Ocean provides a variety of globally important socioeconomic services. Throughout the region, marine primary producers play a role in this disproportionately large carbon sink, thereby buffering the effects of human-caused warming. Understanding the fate of productivity throughout the North Atlantic is therefore critical for forecasting future climate. The historically large abundance of commercially relevant marine species in the region has also attracted numerous industrial fisheries. However, due to a lack of effective regulations, fishery overexploitation became rampant in the early-to-mid-twentieth century and eventually resulted in the dramatic crash of Atlantic cod populations. Sparse observational evidence suggests that this twentieth-century removal of Atlantic cod drove ecosystem-wide changes, ultimately resulting in increased productivity throughout previously overfished areas. To systematically evaluate these ecological links and their possible additional connections to climatic variability, we will build a new database linking historical catch statistics to geological records of productivity and past climate.